Applications of multiple musical intelligence in learning process of special education needs student with hearing impairment - Magiman, Mohamad Maulana; Nordin, Mohd Norazmi; Rajoo, Murugan; Mohd Yunus, Yusmi; Maidin, Siti Sarah; Abbas, Mohd Saleh (African Science Publications, 2024)
Multiple Musical Intelligence, as presented by Howard Gardner, refers to intelligence that involves the ability to understand, create, and appreciate music from various aspects (Gardner, 1998). An individual with musical intelligence will naturally be more inclined towards music. Individuals with musical intelligence will show a rich interest in identifying musical rhythms and melodies, knowing patterns in music, and being able to create or improvise with music. In addition, musical intelligence is not limited to playing or creating music using various musical instruments; it also involves an appreciation of music and the ability to use music to evoke various emotions or moods in daily life.